Zhodnocení finanční situace podniku a návrhy na její zlepšení - Skoupá, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce se zabývá zhodnocením finanční situace společnosti SINCLAIR Global Group s.r.o. v letech 2017-2021. První část je zaměřena na vymezení hlavního cíle, dílčích cílů a metodiky. Další část je věnována teoretickým východiskům, kde jsou definovány základní teoretické pojmy. Z teoretické části následně vychází praktická část. V praktické části je charakterizována společnost (historie, předmět podnikání, organizační struktura) a dále jsou zde použity metody na zhodnocení finanční situace společnosti. Poslední část je věnována vlastním návrhům řešení na zlepšení finanční situace.

The bachelor thesis deals with the evaluation of financial situation of the company SINCLAIR Global Group s.r.o. in the years 2017-2021. The first part is focused on the definition of the main objective, sub-objectives and methodology. The next part is devoted to the theoretical background, where the basic theoretical concepts are defined. Subsequently, the practical part is based on the theoretical part. In the practical part, the company is characterized (history, subject of business, organizational structure) and then the methods are used to evaluation of the financial situation of a company. The last part is devoted to the proposals for improvement of the financial situation.
Evaluation of the Financial Situation of a Company and Proposals for Improvement
Keywords: Finanční analýza; rozvaha; výkaz zisků a ztrát; likvidita; rentabilita; Financial analysis; balance sheet; profit and loss statement; liquidity; profitability